Implementasi Ekstrakurikuler Keagamaan di SMKN-1 Palangka Raya - Lilik Kholisotin; Minarsih Minarsih (Anterior Jurnal, 2018)
Extracurricular implementation is an additional activity carried out at the school outside of the school hours. Through extracurricular activities, students are expected to develop talents and interests in accordance with their respective fields. This study aims to find out how the implementation of extracurricular diversity, what are the supporting factors and obstacles in its implementation, as well as how the impact after the implementation of religious extracurricular activities at the Palangka Raya Vocational High School 1 implemented. The method used in this study is a qualitative approach. The researcher used several data collection techniques, namely observation, interviews, and documentation. The results showed that extracurricular activities implemented at Palangka Raya Vocational High School 1 consisted of three types of activities, namely activities namely reading Iqra ', calligraphy, and habsyi. Supporting factors in the implementation of religious extracurricular activities at SMKN-1 are the existence of professional PAI teachers, active students, extracurricular guidance teachers in their fields, and facilities and infrastructure that support and accommodate the implementation of extracurricular activities. While the inhibiting factors in this implementation are the low participation of students, lack of sufficient time available, lack of teaching staff in their fields, availability of funds, and guidance teachers not on time. Furthermore, the impact of extracurricular religious implementation in SMKN-1 is a better change as evidenced by the success of students being able to read the Qur'an, knowing how to write calligraphy that is good and true and increasing knowledge and changing attitudes and training skills according to students' talents.